ELAB:end-host-based congestion aware load balancing for data center network - Guo CHEN; Weifeng ZHANG (Tongxin xuebao)
A good load balance mechanism is the key to effectively use the network of the data center network.In current production data center,ECMP is the de facto load balancing scheme.However,it has two drawbacks.1) the load balance unit is too coarse-grained,2) it’s not congestion aware.To solve these problems,several fine-grained and congestion-aware load balancing works have emerged in recent years.These works either need to modify the switch hardware to collect congestion in various parts of the network in real time,and it is difficult to deploy; or only need to modify the end system,but the inaccurate sense of congestion cannot achieve a good load balancing effect.A novel edge-based load balancing scheme ELAB was proposed,which addresses above existing problems and improves the network performance up to 20%.